Returns to Late Aged College Degrees - Wallace, Sally; Mroz, Thomas; Hathaway, Alex (International Journal of Population Data Science, 2018)
The benefits of a college education are well documented. However, the majority of existing research focuses on students who matriculate soon after high school graduation. There is little empirical evidence illustrating whether a college degree is similarly beneficial to those already in the workforce, particularly individuals over 50. Nonetheless, the coming years will see the dramatic growth of older individuals, many of whom will continue to be active in the labor force, and policymakers would benefit from effective strategies to improve the labor market outcomes of older individuals. This research proposes to evaluate the labor market outcomes of individuals in Georgia who obtain a bachelor’s degree at age 50 or older by merging state-level individual level labor force (Dpt of Labor) with individual level educational data from the University System of Georgia (USG). Specifically, we explore whether these later-age degrees result in employment opportunities with higher wages and increased retention in the labor force beyond the traditional retirement age of 65 than those who do not attain a bachelor’s degree. The results will provide policymakers across the United States with information to make informed decisions regarding higher education incentives and policies for older students.